Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acsnano.1c04925
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nuclear Localization Sequences on the Intracellular Fate of Gold Nanoparticles

Abstract: Directing nanoparticles to the nucleus by attachment of nuclear localization sequences (NLS) is an aim in many applications. Gold nanoparticles modified with two different NLS were studied while crossing barriers of intact cells, including uptake, endosomal escape, and nuclear translocation. By imaging of the nanoparticles and by characterization of their molecular interactions with surface-enhanced Raman scattering (SERS), it is shown that nuclear translocation strongly depends on the particular incubation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“… 82 Combined SERS and electron microscopy data indicated that the nanoparticles are processed differently in the endolysosomal system when they carry an NLS, even when they do not undergo endosomal escape. 82 In the situation where endosomal escape does not take place, the endosomal molecular composition and interaction of the modified gold nanoparticles resembles that of unmodified nanoparticles. At the same time, the SERS spectra indicated special molecular properties of the intracellular agglomerates, which was related to their ‘attempt’ to engage in endosomal escape.…”
Section: Probing Different Cellular Compartmentsmentioning
confidence: 99%
See 3 more Smart Citations
“… 82 Combined SERS and electron microscopy data indicated that the nanoparticles are processed differently in the endolysosomal system when they carry an NLS, even when they do not undergo endosomal escape. 82 In the situation where endosomal escape does not take place, the endosomal molecular composition and interaction of the modified gold nanoparticles resembles that of unmodified nanoparticles. At the same time, the SERS spectra indicated special molecular properties of the intracellular agglomerates, which was related to their ‘attempt’ to engage in endosomal escape.…”
Section: Probing Different Cellular Compartmentsmentioning
confidence: 99%
“…76,80 The success in probing the intracellular environment in this case depends greatly on whether and which molecules are used for potential functionalization, how they change the uptake dynamics and how accessible the particle surface remains. 58,81,82 Cells incubated with gold nanoparticles functionalized with polyadenine show different interactions within the same incubation period as non-functionalized particles. 81 While the bare gold nanoparticles interact mainly with lipids after 4 h, and for longer incubation times lipid bands decrease and protein and 15 nucleic acid related bands increase, functionalization with polyadenine results in a decreased interaction with lipids at shorter times and faster appearance of protein related bands in the spectra, suggesting that this functionalization facilitates cellular uptake of nanoparticles and induces a faster formation of endosomes.…”
Section: Nanoscale Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Phototherapeutic nanodrugs can be passively targeted to the nucleus by changing surface properties and size because of the highly physicochemical flexibility of nanomaterials ( Jiang et al, 2020 ; Xu et al, 2020 ). More importantly, active targeting of the nucleus can also be achieved by modifying nucleus-targeting groups such as cell-penetrating peptides [e.g., transactivator of transcription (TAT)] ( Su et al, 2020 ; Tietz et al, 2022 ), the specific nuclear localization signal/sequence (NLS) peptide ( Zelmer et al, 2020 ; Drescher et al, 2021 ), and DNA aptamers ( Dong et al, 2018 ; Yang et al, 2018 ; Zeng et al, 2020 ) on phototherapeutic nanodrugs. Apart from this, ROS generated by phototherapeutic nanodrugs can also damage the membrane structure to increase permeability ( Chen et al, 2021 ; Su et al, 2021 ; Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%